TRANSFORMASI HUKUM ADMINISTRASI DI ERA DIGITAL TANTANGAN DAN PELUANG UNTUK PEMERINTAHAN YANG TRANSPARAN DI KOTA PROBOLINGGO - Satunggale Kurniawan (Journal Of Law And Social Society, 2025)
The transformation of administrative law in the digital era presents challenges and opportunities for transparent governance. The development of information and communication technology has changed the way government administration provides services to the public. Digitalization of public administration not only enhances bureaucratic efficiency and effectiveness but also demands legal reforms to ensure accountability and the protection of citizens' rights. This study aims to analyze the impact of administrative law transformation in the digital era on government transparency and identify emerging challenges and opportunities. By understanding these changes, this research seeks to provide policy recommendations for creating a more transparent and accountable administrative system. The research employs a qualitative method with a descriptive-analytical approach. Data were collected through literature studies, analysis of legal regulations, and interviews with legal and public administration experts. The findings were then evaluated based on administrative law theories and the principles of good governance. indicate that the digitalization of government administration significantly contributes to increased transparency, efficiency, and accountability. However, several challenges must be addressed, such as data protection, digital divide, and resistance to change within the bureaucracy. Therefore, adaptive regulations and supportive policies are needed to ensure justice, openness, and public participation in governance.